Influência da calagem e do fósforo na adubação de culturas com zinco I- sorgo - Braga, José Mário (Revista Ceres, 2025)
The objectives of this study were to analyze the effects of the interactions among zinc, phosphorus, lime, type of soil, and sorghum variety in the production of dry matter; and, to measure the phosphorus and zinc contents in the aerial parts of sorghum varieties.